Enhanced Photocatalytic degradation of methyl orange using Ag-doped TiO2 photocatalyst - Lim, Ying Chin; Lim, Ying Pei; Kanakaraju, Devagi; Huey, Ling Tan (Medwell Publishing, 2018)
In the present study, Ag-doped Titanium dioxide (Ag-TiO2 ) photocatalyst was prepared by wet impregnation method. The effect of dopant concentration, incubation temperature and incubation time on the photocatalytic degradation of Methyl Orange (MO) in aqueous suspension under Ultra Violet (UV) light irradiation were studied systematically. The synthesized photocatalyst was characterized using XRD and SEM-EDX mapping. The characterization results confirmed that Ag was successfully doped into TiO2 with anatase phase structure. The Ag-TiO2 photocatalyst exhibited the highest dye removal of 85% efficiency with 5 wt.% dopant concentration when the incubation temperature and time were 70C and 8 h, respectively. The kinetic study revealed that photocatalytic reaction follows Langmuir Hinshelwood (L-H) Model and pseudo-first order law with the highest regression coefficient of 0.992. Ag-TiO2 was found to be an efficient photocatalyst showing enhanced photocatalytic activity for MO decolorization under UV irradiation.